Dynamical Inverse Problems Theory and Application - Gladwell, Graham M. L.; Morassi, Antonino; SpringerLink (Online service). (Vienna Springer Vienna, 2011)
The papers in this volume present an overview of the gerneral aspects and practical applications of dynamic inverse methods, through the interaction of several topics, ranging from classical and advanced inverse problems in vibration, isospectral systems, dynamic methods for structural identification, active vibration control and damage detection, imaging shear stiffness in biological tissues, wave propagation, to computational and experimental aspects relevant for engineering problems.
Keywords: Electronic books; Engineering; Differentiable dynamical systems; Systems theory; Civil Engineering; Systems Theory, Control; Vibration; Inverse problems (Differential equations); Mathematics; Dynamical Systems and Ergodic Theory